Impact of Perceived Destination Personality on Tourists’ Behavior - R., Sabari Shankar (Prabandhan: Indian Journal of Management, 2020)
This research paper attempted to study the influence of tourists’ perception about the destination personality traits on their behavior. Fierce global competition in the tourism market and the significant requirement of research contribution to destination branding arena were the primitive motives of this research. Intensive review supporting the objective was carried out and a theoretical model was found. To validate it, Coimbatore â€“ a district in Tamil Nadu, India was chosen. This study was conducted between 2018 and 2019 targeting the tourists who visited the destination. A well-defined questionnaire was designed, perhaps finalized after the pilot study, and was floated to 570 tourists using convenient sampling technique. The questions seeking tourists’ personal factors as well as statements measuring destination personality traits and tourists’ behavior were contained in the questionnaire. Responses were screened and illegible filled-in questionnaires were removed and thereby 448 was fixed as the sample. To achieve the objective, a three - stage analysis was performed. Data analysis tools such as exploratory factor analysis using SPSS was used for data reduction, confirmatory factor analysis and structural equation modeling of AMOS were used for confirming the existence of individual model in each factor and to validate the theoretical model, respectively. As a key outcome, the model was validated with two constructs measuring destination personality and three constructs measuring tourists’ behavior and all the necessary values were in an acceptable range. Also, it was found that perceived destination personality had a significant influence on tourists’ behavior. Marketers are suggested to inculcate the key aspects of this research work in their destination marketing, branding, and promotional activities.